2019
DOI: 10.6007/ijarbss/v9-i5/5842
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural factors affecting Women Economic Empowerment in Pakistan: A Situation Analysis

Abstract: Women empowerment is a global key concern in terms of development. It has various shapes over the time and space but closely connected to the economic, socio-cultural, familial or interpersonal, legal, political, and psychological domains. Pakistan like many other countries have signatory of several international declarations till now to empower the women, but at the same time Pakistani women experience high level of discriminations and economic dependency is one of them. A variety of academic literature is av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…The key Critical indicator in the process of women empowerment is decision making. In FATA, it is observed that empowerment of women has a positive relationship with the place of residence, women of old age, BISP, fertility preferences and ownership of property (Choudhry, 2019;Mustafa, 2019;Osiewalska, B. 2018;Strzelecka, 2017;Mubeen et al, 2019;Raza et al, 2021).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The key Critical indicator in the process of women empowerment is decision making. In FATA, it is observed that empowerment of women has a positive relationship with the place of residence, women of old age, BISP, fertility preferences and ownership of property (Choudhry, 2019;Mustafa, 2019;Osiewalska, B. 2018;Strzelecka, 2017;Mubeen et al, 2019;Raza et al, 2021).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Women education enhances the quality and standard of women inside and outside their homes. Women education not only defines how many girls are enrolled in schools but It's about ensuring that girls gain knowledge and feel secure while in educational institutions; have the opportunity and access to complete all levels of education from primary to higher levels, getting knowledge and skills to participate in labor market, learn the socio-economic skills to compete the contemporary world, feel free to decide about their personal matters and contribute in the wellbeing of their family and society (Choudhry, et al, 2019a). Education helps in reduction of inequalities by improving the status and position of women in the society by giving them space and opportunities to participate in the social and development sectors.…”
Section: Review Of Literature Women Educationmentioning
confidence: 99%
“…Social taboos do not allow women to have access to a decent job or employment. Uneducated women are more prone to violence and abuses, mostly families also deprive their daughters from property rights (Choudhry, et al, 2019b).According to a report of Oslo Summit on Education resource distribution in education sector of Pakistan is of a serious concern. The federal government should increase the educational resources of least developed provinces, and the distribution of resources within the provinces is also necessary (Dr. Rabea Malik, 2015).From this part of literature, we perceive that women in in Pakistan face discrimination and hurdles while receiving higher education.…”
Section: Challenges To Women Education In Pakistanmentioning
confidence: 99%
“…Due to social pressures, families do not allow women to have a job. Women are mostly denied property rights which discourage and obstruct their development and growth (Choudhry, Mutalib, & Ismail., 2019). The data also concedes with the literature review.…”
Section: 3: Women Should Be Permitted To Do Business Out Of Chitralmentioning
confidence: 99%
“…Abubakar Nazeer Chaudhry (2019) highlights the effects of social norms and cultural constraints as "Social and Cultural taboos inversely affect women better upbringing. Societal and familial factors of not letting women do a decent job will affect the social fabric of the whole country while blocking the avenues of peace and prosperity (Choudhry, Mutalib, & Ismail 2019). To pursue higher education women face lots of challenges like; burden of house chores, harassment at workplaces, socio-cultural misunderstandings, and financial constraints (Murtaza, 2012).…”
mentioning
confidence: 99%